Stiffness loss in laminates with intralaminar cracks. Part I. Two-dimensional modelling - Lewiński, T.; Telega, J.J. (Archives of Mechanics, 1996)
By imposing stress constraints of Hashin type and corresponding kinematic constraints on the Reissner two-field functional, a new two-dimensional model for the three-layer symmetric laminate is derived. This model is capable of taking into account transverse cracks in the internal layer. These cracks behave according to Signorini’s conditions. In Part I the basic properties of the model without and with transverse crack in the internal layer are investigated. The equilibrium problem is governed by a variational inequality involving five kinematic unknowns.